Implementasi PHP Web Service Sebagai Penyedia Data Aplikasi Mobile - Martinus Raditia Sigit Surendra (Ultimatics : Jurnal Teknik Informatika, 2014)
This paper demonstrates how PHP web service technology can be used in mobile application. Web service testing can be done manually by creating php client file that call the SOAP web service. Testing can also be done using SoapUI, an open source software that can be used to do functional testing on web service. This paper is proof of concept that PHP Web Service can be used as data provider for application that need dynamic data. This paper proposed PHP Client Layer as an additional layer to simplify the web service calling from mobile application. Index Terms - web service, php, json, SOAP, SoapUI